Depressive symptoms and children’s resilience - Castro Gomero, Carla Jimena (2018)
The aim of this research is to show the relationship between the depressive symptomatology and the resilience in an Educational Institution of Lima metropolitan area. This research was carried by applying Children’s Depression Inventory (Kovacs, M., 2004) and the Resilience Personal Factors Inventory (Salgado, A., 2005). The sample used consisted of 146 children from 3rd, 4th, and 5th grade of Elementary School, whose ages ranged between 8 and 10 years old. This is a descriptive, and non- experimental design- transversal- correlational research; having as result that when more depressive symptomatology; less resilience there is, showing a reverse correlation.